2006
DOI: 10.4314/sajas.v36i2.3997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between sexual maturity and weekly live-weights in laying-type Japanese quail

Abstract: This study focused on the estimation of genetic relationships between weekly live weights and sexual maturity of male and female Japanese quail. The live body weight data of a laying-type quail line over time were collected from hatching to six weeks of age. Sexual maturity was determined as the day of production of cloacal gland foam for males, and the day of laying the first egg for females. (Co)Variance components and genetic parameters were estimated, using MTDFREML, a restricted maximum likelihood (REML) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
8
12
1
Order By: Relevance
“…Sexual dimorphism has previously been reported in favour of the male in duck [23], pigeon [24], and pheasants [25,26]. The growth pattern of male and female Japanese quails raised in other environments have been well documented [20,[27][28][29]. The growth pattern observed in the present study agrees with the pattern reported in refs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sexual dimorphism has previously been reported in favour of the male in duck [23], pigeon [24], and pheasants [25,26]. The growth pattern of male and female Japanese quails raised in other environments have been well documented [20,[27][28][29]. The growth pattern observed in the present study agrees with the pattern reported in refs.…”
Section: Discussionsupporting
confidence: 91%
“…[16,17] who reported that the age is a major determinant of growth and physiological development. The body weight and linear measurements obtained in this study were however lower than values reported by other authors [18][19][20][21].This is not unexpected in morphometric traits assessments of birds belonging to different populations [22]. The coefficient of variation for morphometric traits suggest that there was an increased uniformity in body size measurements as the birds advance in age, especially among the female quails.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…According to Sezer et al (2006), the initial growth pattern and body weight at sexual maturity are the main factors which affect the performance of birds in the laying phase.…”
Section: Introductionmentioning
confidence: 99%